Pengaruh Servant Leadership, Motivasi dan Kepuasan terhadap Loyalitas Kerja Karyawan pada Plataran Canggu Bali Resort & Spa - Ni Ketut Lia Sukma , Dewi; Christimulia Purnama , Trimurti; Ni Putu Dyah , Krismawintari (LPPM Universitas Dhyana Pura, 2024)
In a hotel accommodation, there are employees who work to serve and provide information to guests, able to achieve success and determine the development of the company. Each employee has their own Job Loyalty and to increase Work Loyalty. The aim of this study was to determine the effect of Servant Leadership on motivation, and Job Satisfaction on Job Loyalty at Plataran Canggu Bali Resort & Spa with a population of 60 employees. Data analysis was performed by using the regression test. The research results showed 1) servant leadership has a significant positive effect on employee loyalty, with a t-count value of 24.248 > t-table value of 1.67 and a significance of 0.000 <0.05. 2) motivation has a significant positive effect on customer satisfaction, with a t-count value of 12.758 > t-table value of 1.67 and a significance of 0.000 <0.05. 3) satisfaction has a significant positive effect on work loyalty, with a t-count value of 13.114 > t-table value of 1.67 and a significance of 0.000 <0.05. 4) simultaneously servant leadership, motivation and satisfaction have a significant effect on employee loyalty at Plataran Canggu Bali Resort & Spa, with an f-count value of 349.770 > f-table value of 2.77 and a significance of 0.000 <0.05. Based on these results it can be concluded that servant leadership, motivation and satisfaction partially and simultaneously affect employee loyalty at Plataran Canggu Bali Resort & Spa with a contribution of 94.7%.